Hydrogen production from steam gasification of corn straw catalyzed by blast furnace gas ash. (10th July 2020) - Pang, Yunji; Yu, Donling; Chen, Yisheng; Jin, Guang; Shen, Shengqiang
Abstract: A lab scale gasifier was built to perform the gasification experiment. The effects of temperature and steam flow on the process were investigated, and the effects of the addition of blast furnace gas ash (BFGA) on product composition, the value of H2 /(CO + CO2 ), the lower heating value (LHV) of product gas, and productivity are summarized. The experimental results clearly indicate that the addition of BFGA in the steam gasification of corn straw pellets effectively enhances the ability of the downdraft gasifier to produce hydrogen-rich gas. Compared with the non-catalytic gasification process, the addition of BFGA promotes the formation of H2, inhibits the generation of methane, CH4, and other hydrocarbon gases, Cn Hm, and increases the H2 /(CO + CO2 ) ratio. Unlike the process without the BFGA, the LHV of the product gas with BFGA increases with increasing temperature. When the water vapor volume was 0.75 kg/h, the gas production rate was the same at 850 °C with BFGA and at 950 °C without ash gas. The addition of BFGA clearly leads to a significant improvement in the ability of gasifiers to produce hydrogen-rich gas. Highlights: The blast furnace gas ash improves the capacity of gasifier. The catalytic reforming of the char layer is intensified, and H2 content is improved. Temperature and S/B have a stronger influence on product gas characteristics.